Seleção de genótipos resistentes de amendoinzeiro a Anticarsia gemmatalis Hübner (Lepidoptera: Noctuidae) com base em análises multivariadas - Pitta, Rafael M.; Boiça Júnior, Arlindo L.; Jesus, Flávio G. de; Tagliari, Sônia R. A. (Springer Nature, 2010)
The velvetbean caterpillar Anticarsia gemmatalis Hübner attacks peanut leaves, and the use of resistant varieties has directly contributed to ecological and economic aspects of pest control. The aim of this work was to select resistant peanut genotypes to A. gemmatalis using cluster analyses (dendogram obtained by Ward's methods and K-means) and Principal Components analysis for data interpretation. The evaluated genotypes were: IAC 5, IAC 8112, IAC 22 and IAC Tatu ST with upright growth habit, and IAC 147, IAC 125, IAC Caiapó and IAC Runner 886 with runner growth habit, and soybean genotype BR 16 as a susceptible control. The biological parameters: leaf consumption, larval (4o instar) and pupal (24h old) weight, larval and pupal development time and adult longevity were evaluated at laboratory conditions. The genotypes IAC 147 and IAC Runner 886 were resistant to A. gemmatalis in both cluster tests, grouping apart from most of the other genotypes. Both dendrogram and K-means methods provided satisfactory biological explanation, and they can be complementary used together with Principal Component and vice-versa. These results suggest that cluster analyses may be an important statistical tool in the selection of host plant resistance.
Selection of resistant peanut genotypes to Anticarsia gemmatalis Hübner (Lepidoptera: Noctuidae) supported by multivariate analysis
Keywords: Arachis hypogea; Biological parameter; Host plant resistance; Velvetbean caterpillar; animal; genetics; genotype; innate immunity; Lepidoptera; multivariate analysis; parasitology; peanut; Animals; Arachis hypogaea; Genotype; Immunity, Innate; Multivariate Analysis; Anticarsia gemmatalis; Glycine max; Noctuidae